2006
DOI: 10.1021/jp0609479
|View full text |Cite
|
Sign up to set email alerts
|

Product and Pulse Radiolysis Studies on Radical-Ion Splitting of N(1)−C(5‘)-Linked Dimer Hydrates of 5-Substituted Uracils by One-Electron Reduction in Anoxic Aqueous Solution

Abstract: Steady-state gamma-radiolysis, pulse radiolysis, and cyclic voltammetry have been performed to identify the mechanism by which N(1)-C(5')-linked homodimer hydrates [1-(6'-hydroxy-5',6'-dihydrothymin-5'-yl)thymine (2a) and [1-(5'-fluoro-6'-hydroxy-5',6'-dihydrouracil-5'-yl)-5-fluorouracil (2b)], N(1)-C(6')-linked dimer hydrate [1-(5'-hydroxy-5',6'-dihydrothymin-6'-yl)thymine (3a)], and N(1)-C(5')-linked heterodimer hydrate [1-(6'-hydroxy-5',6'-dihydrothymin-5'-yl)-5-fluorouracil (2ba)] undergo radiolytic reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…16,17 In addition, transient absorption spectroscopy has been widely used for the direct observation of the carbon-centered radicals formed in the reactions. 1,5,9,15,18,19 Regarding the latter technique, the spectra related to the pyrimidine nucleobases 1, 9 and some of their derivatives as 5,6-dihydrouracil or 1,3-dimethyluracil 9 in aqueous solution were reported early in 1970s. For uracil, a broadband centered at around 3.26 eV (380 nm) was observed at pH 3.15.…”
Section: The Journal Of Chemical Physics 139 071101 (2013)mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In addition, transient absorption spectroscopy has been widely used for the direct observation of the carbon-centered radicals formed in the reactions. 1,5,9,15,18,19 Regarding the latter technique, the spectra related to the pyrimidine nucleobases 1, 9 and some of their derivatives as 5,6-dihydrouracil or 1,3-dimethyluracil 9 in aqueous solution were reported early in 1970s. For uracil, a broadband centered at around 3.26 eV (380 nm) was observed at pH 3.15.…”
Section: The Journal Of Chemical Physics 139 071101 (2013)mentioning
confidence: 99%
“…In this scenario, a systematic study on the · OH adducts of the pyrimidine nucleobases and the H-abstraction products of 5,6-dihydrouracil using accurate ab initio multiconfigurational methods that include dynamic correlation seems to be timely. Our motivation has also been enhanced by new experimental works in which transient absorption spectroscopy 19,24 has been employed to study nucleicacid damage. DNA/RNA oxidation by · OH radical remains a field of active research.…”
Section: The Journal Of Chemical Physics 139 071101 (2013)mentioning
confidence: 99%
“…Radiolytic reduction of the dimer hydrate 33 by e aq − regenerates 5FU, along with 1-(uracil-5 -yl)-5-fluorouracil (34). 66 The pulse radiolysis study demonstrated a one-electron reduction mechanism by which a radical anion in the form of an electronadduct at the 5FU moiety is generated as the initial intermediate during radiolytic reduction, followed by F − elimination from the radical anion and hydrolytic splitting of N1-C5 linkages to regenerate 5FU. 66 Further one-electron reduction can occur competitively from the radical [33(-F) • ] into a byproduct 34.…”
Section: N-methyl-n-[(1-methyl-4-nitro-5-imidazoyl)methyl]ammonium Ch...mentioning
confidence: 99%
“…66 The pulse radiolysis study demonstrated a one-electron reduction mechanism by which a radical anion in the form of an electronadduct at the 5FU moiety is generated as the initial intermediate during radiolytic reduction, followed by F − elimination from the radical anion and hydrolytic splitting of N1-C5 linkages to regenerate 5FU. 66 Further one-electron reduction can occur competitively from the radical [33(-F) • ] into a byproduct 34. The reduction mechanism of pyrimidine dimer has provided a novel strategy of radiation-activated 5FU prodrugs for the treatment of malignant hypoxic solid tumors (Scheme 2).…”
Section: N-methyl-n-[(1-methyl-4-nitro-5-imidazoyl)methyl]ammonium Ch...mentioning
confidence: 99%
“…Recently we have proposed caged drugs (prodrugs) that are activated by hypoxic X-irradiation. [7][8][9][10][11] Our studies illustrated that a 2-oxoalkyl group has an effective functionality for caging antitumor drugs such as 5-fluorouracil (5-FU) 8,9 and 5-fluorodeoxyuridine (5-FdUrd), 10 and for radiolytic activation of the resultant caged drugs. This class of radiation activated caged drugs release the 2-oxoalkyl group by reducing hydrated electrons, which are generated as the major active species along with hydrogen atoms and hydroxyl radicals upon radiolysis of an aqueous solution.…”
mentioning
confidence: 96%